Urgensi Penanaman Nilai-Nilai Islam dalam Upaya Menangkal Isu Internasional: LGBT Pada Ikatan Remaja Masjid Sabilul Jannah - Fatmawati; Rizal Effendi Putra; Rinah; Muhammad Irham; Roza Andriani (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Sabilul Jannah Mosque is a mosque located in Tirta Siak Village, Payung Sekaki District, Pekanbaru City, Riau Province. At the mosque, there is a group of mosque youth who still do not know clearly and in detail about the dangers of international issues: LGBT and the application of Islamic values ​​in an effort to prevent the dangers of LGBT. The purpose of the social service activities is first, to increase knowledge of the dangers of LGBT at the Sabilul Jannah Mosque Youth Association. Second, to increase insight into the urgency of the application of Islamic values ​​in an effort to prevent the dangers of international issues: LGBT in Sabilul Jannah Mosque Youth Association. This service activity was carried out at Sabilul Jannah Mosque.